Attention to Monocular Images Bias Binocular Rivalry - Moreno-Sánchez, Manuel; Aznar-Casanova, J. Antonio; Valle-Inclán, Fernando (Frontiers in Systems Neuroscience, 2019)
When monocular images cannot be fused, perception alternates between the two (or more) possible images. This phenomenon, binocular rivalry (BR), is driven by the physical properties of the stimuli (size, contrast, spatial frequency, etc.) but it can also be modulated by attention to features of one of the rival stimuli (Chong, Tadin, & Blake, 2005; Dieter, Melnick, & Tadin, 2016) and by attentional demands independent of the BR assessment (Paffen, Verstratenm & Vidnyánszky, 2008). Instead of the perceptually demanding tasks previously used to bias BR, we designed a simple counting task. We monocularly presented a number of trials (around 10 min) with a set of symbols and asked participants to count them. We found that after this task, dominance durations decreased for the unattended channel, and did not change for the attended channel. The results parallel those of Paffen et al. (2008) and square nicely with Levelt’s second proposition, suggesting that the counting task effectively increased the sensibility of one channel which led to increased strength of the images presented to that channel. Alternatively, the results could be explained assuming that the non-attended channel was inhibited during the counting task, and the inhibition was carried over to the BR task.